Near-band-edge emission of mechanically milled and thermally annealed ZnO:Ge particles - HN Van (2020)
This paper reports a novel way for the synthesis of Ge-doped ZnO particles by a mechanically milled Ge and ZnO powder mixture (ZnO:Ge) followed by thermal annealing in Ar + 5%H2 to achieve near-band-edge (NBE) emission of ZnO with controllable intensities. The Ge-doped ZnO particles were synthesized by mechanical milling of a ZnO and Ge powder mixture up to 50 h in particularly, using different ZnO:Ge ratios and annealing temperatures. The Ge-doped ZnO particles were observed to have a rounded morphology with a diameter of ~500 nm when an annealing temperature of 1000°C was used. The Ge-doped ZnO particles showed NBE emission of ~380 nm with a suppressed visible band of ~500 nm as a function of the Ge content and annealing temperatures. These results suggest that the current method is very useful for synthesis of Ge-doped ZnO particles to obtain NBE emission, which is of particular importance for potential application in the optoelectronic and UV detector field.